Installation method of unipaver interlocking paver / Nur Fatihah Murad - Murad, Nur Fatihah (Universiti Teknologi MARA UiTM,Perak, 2022)
Each paver in an interlocking paver system is designed to fit together like puzzle pieces. Interlocking pavers are able to install without mortar because they fit tightly together (Types of Interlocking Pavers, n.d.). Interlocking pavers are available in a wide range of shapes, sizes, and color, but it may be divided into three categories based on the materials they’re built of. The aim of this report was conducted for the maintenance work including the removal and installation of unipaver interlocking paver throughout at the parking area of Telok Bahang Recreational Park (Taman Rimba), Penang. The objective of this report is to determine the installation method and to identify the advantages of using interlocking. The study will cover the method and the procedures used for this maintenance work.